The Meeting Line of the Body and the Soul. Notes About the Flesh in the Project of a History of Sexuality; [la Línea de Unión Entre el Cuerpo y el Alma. Notas Sobre la Cuestión de la Carne en el Proyecto de Una Historia de la Sexualidad] - Arancibia-Carrizo, J (CSIC Consejo Superior de Investigaciones Cientificas, 2024)
The proposal reviews some thematic notes as an overall perspective of the project of a History of sexuality. In this sense, the notion of the body as affected by power and force allows a link with the notion of flesh. A path is thus established that considers, at first, the characteristics that the body takes from a genealogical perspective. A second question is about the particular form of forces in the context of ancient Greece composed of free men. In a third moment, the body is analyzed as an instance which, in the face of the technologies of power, gives shape to a dimension that is simultaneously individual and social. In another moment, the body is examined as a place that allows a reading of sexuality as a discursive inscription which the truth of the subjects appears. © 2024 CSIC.